Nucleus preservation in early Ediacaran Weng'an embryo-like fossils, experimental taphonomy of nuclei and implications for reading the eukaryote fossil record. Issue 4 (12th June 2020) - Sun, Weichen; Yin, Zongjun; Cunningham, John A.; Liu, Pengju; Zhu, Maoyan; Donoghue, Philip C. J.
Abstract : The challenge of identifying fossilized organelles has long hampered attempts to interpret the fossil record of early eukaryote evolution. We explore this challenge through experimental taphonomy of nuclei in a living eukaryote and microscale physical and chemical characterization of putative nuclei in embryo-like fossils from the early Ediacaran Weng'an Biota. The fossil nuclei exhibit diverse preservational modes that differ in shape, presence or absence of an inner body and the chemistry of the associated mineralization. The nuclei are not directly fossilized; rather, they manifest as external moulds. Experimental taphonomy of epidermal cells from the common onion ( Allium cepa ) demonstrates that nuclei are more decay resistant than their host cells, generally maintaining their physical dimensions for weeks to months post-mortem, though under some experimental conditions they exhibit shrinkage and/or become shrouded in microbial biofilms. The fossil and experimental evidence may be rationalized in a single taphonomic pathway of selective mineralization of the cell cytoplasm, preserving an external mould of the nucleus that is itself resistant to both decay and mineral replication. Combined, our results provide both a secure identification of the Weng'an nuclei as well as the potential of a fossil record of organelles that might help arbitrate in long-standing debates over the relative and absolute timing of the evolutionary assembly of eukaryote-grade cells.